2018
DOI: 10.1007/s00296-017-3916-x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in systemic sclerosis: data from the spanish scleroderma study group

Abstract: Our study indicates that ILD constitutes a remarkable complication of SSc with significant morbidity and mortality, which should be borne in mind in all three subgroups (lcSSc, dcSSc, and ssSSc).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 40 publications
0
36
1
3
Order By: Relevance
“…Studies in patients with progressive fibrosing ILDs have identified several factors that predict mortality, but these need to be interpreted carefully given the variation in the methodology used and the retrospective nature of most of the studies. Lower FVC is an established predictor of mortality in patients with progressive fibrosing ILDs, as evidenced by numerous studies spanning IPF [55][56][57], RA-ILD [4,49], SSc-ILD [58][59][60], chronic HP [61,62] and fibrotic iNSIP [53]. The same is true of DLco [55,56,60,[63][64][65], although this is harder to assess in multi-center studies due to a lack of standardization in its measurement.…”
Section: Predictors Of Disease Progression In Patients With Fibrosingmentioning
confidence: 99%
“…Studies in patients with progressive fibrosing ILDs have identified several factors that predict mortality, but these need to be interpreted carefully given the variation in the methodology used and the retrospective nature of most of the studies. Lower FVC is an established predictor of mortality in patients with progressive fibrosing ILDs, as evidenced by numerous studies spanning IPF [55][56][57], RA-ILD [4,49], SSc-ILD [58][59][60], chronic HP [61,62] and fibrotic iNSIP [53]. The same is true of DLco [55,56,60,[63][64][65], although this is harder to assess in multi-center studies due to a lack of standardization in its measurement.…”
Section: Predictors Of Disease Progression In Patients With Fibrosingmentioning
confidence: 99%
“…When considering patients with SARD as controls, it is important to rule out overlap syndromes 5. One example is the association of AIM with interstitial lung disease, which can occur in myositis and in other SARD and especially systemic sclerosis 6. The differences observed for anti-Jo-1 antibodies are surprising and concerning since those antibodies have been measured for many years,5 and proficiency testing programmes have shown mostly consistent results (eg, https://www.immqas.org.uk).…”
mentioning
confidence: 99%
“…El compromiso pulmonar en las ETC es un problema creciente. Mientras la mortalidad global por ETC parece venir disminuyendo 52,53 , datos actualizados de registros, cohortes y seguros muestran que el compromiso pulmonar en estos pacientes puede estar aumentado e incrementa la morbimortalidad de los enfermos [54][55][56] .…”
Section: Enfermedad Intersticial Asociada a Enfermedad Del Tejido Conunclassified